2013
DOI: 10.1177/1464420713500748
|View full text |Cite
|
Sign up to set email alerts
|

Damping in beams using viscoelastic layers

Abstract: Various types of sandwich beams with viscoelastic cores are currently used in aerospace and automotive industries, indicating the need for simple methods describing the dynamics of these complex structures. In order to understand the effectiveness of the sandwich structures, the dynamics of bare beam with unconstrained and constrained viscoelastic layers are investigated in this study. The viscoelastic layer is bonded uniformly on the beam. The effects of distributed viscoelastic layer treatment on the loss fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…DiTaranto R. [3] and Mead D., Markus S. [4] suggested that for bending and axial vibration the theoretical work on CLD (constrained layer damping) can easily find out. K Kishore Kumar and P Bangarubabu [5] observed that the beams with constrained viscoelastic layer, give higher loss factors values than unconstrained layer. However, the main problem of finding the optimum size of applied constrained layer damping material was not determined.…”
Section: Literature Overviewmentioning
confidence: 99%
“…DiTaranto R. [3] and Mead D., Markus S. [4] suggested that for bending and axial vibration the theoretical work on CLD (constrained layer damping) can easily find out. K Kishore Kumar and P Bangarubabu [5] observed that the beams with constrained viscoelastic layer, give higher loss factors values than unconstrained layer. However, the main problem of finding the optimum size of applied constrained layer damping material was not determined.…”
Section: Literature Overviewmentioning
confidence: 99%
“…The NI-9234 data acquisition (DAQ) system is used to collect the frequency response signals from the accelerometer and are analyzed using LabVIEW software. 10,28,[42][43][44] Results and discussion…”
Section: Fabrication and Dynamic Characterization Of Cgrp-pmc-mrf Cormentioning
confidence: 99%
“…The NI-9234 data acquisition (DAQ) system is used to collect the frequency response signals from the accelerometer and are analyzed using LabVIEW software. 10,28,4244
Figure 6.(a) Schematic view of forced vibration analysis experimental setup and (b) experimental forced vibration analysis setup.
…”
Section: Fabrication and Dynamic Characterization Of Cgrp-pmc-mrf Cormentioning
confidence: 99%
“…Forced vibration analysis using electrodynamic base excitation was performed based on the ASTM E756-05 standard. 10,11,34,35 Figure 20 shows the schematic and photographic view of the experimental forced vibration analysis setup used to determine the excitation amplitude and frequency of the sandwich beams with and without the influence of the magnetic field. The experimental setup consists of 50 kgf electrodynamic shaker, digital switching power amplifier, function generator, single-axis accelerometer sensor, force sensor, NI 9234 DAQ, and LabVIEW 2017 software.…”
Section: Fabrication Of Sandwich Beamsmentioning
confidence: 99%